Value and Aims Of Investing Funds from Operational Programmes 2007–2013 by Rural Communes of Warmińsko-Mazurskie - Rakowska, Joanna (Olsztyn Economic Journal, 2018)
The main aims of the study were to determine the spatial variability of the value of funding absorbed by local self-governments of rural communes (by DEGURBA classification) from operational programmes 2007–2013 per capita (Sci index) and in relation to the average annual budgetary income (Rscr index), as well as to investigate the directions of their use according to the categories specified in the SIMIK database of the Ministry of Development, as of December 31, 2015. All 101 rural communes of warmińsko-mazurskie carried out 697 projects and absorbed 525.4 mln PLN of EU funding from OPs 2007–2013, which made up only 30% of the funding obtained by all communes of this region. The Sci index and Rscr index values reached by this funding ranged from 50 to 5,420 and from 1% to 164% correspondingly. However, most of the communes obtained the lowest values of EU funding placing them in the lowest sub-ranges of these indexes. Only three rural communes reached Rscr values above 100% of their average annual budget revenues. Rural communes of this region benefitted mostly from ‘Regional OP for Warmińsko-Mazurskie’ and from ‘Human Capital OP’, while ‘Innovative Economy OP’ and ‘Infrastructure and Environment OP’ were the sources of least support. Most projects carried out by these communes were either soft-projects or projects resulting in the development of plans and documentation. Hard projects were much fewer, but they still represented as many as 19 SIMIK priorities and met different development needs.